1980
DOI: 10.1002/bip.1980.360190908
|View full text |Cite
|
Sign up to set email alerts
|

1H‐ and 13C‐nmr studies on caffeine and its interaction with nucleic acids

Abstract: SynopsisThe relative orientation of caffeine in stacks formed by self-association in aqueous solution has been evaluated by both 'H-and I3C-nmr spectroscopy. The data, which were interpreted through the calculation of ring-current and atomic diamagnetic anisotropic effects of the caffeine molecule, suggest two caffeine bases may stack in a nearly orthogonal manner. The interactions between caffeine and adenylyl-3',5'-adenosine, polyadenylic acid, and ribo-(A-A-G-C-U-U)Z helix were also studied by nmr at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Instead, it strongly promotes nonspecific binding by UvrA as evidenced by the striking protection of the whole fragment (damaged or undamaged) from DNase I digestion when both UvrA and caffeine are present. We can also detect caffeine-dependent binding of (20)(21)(22), and it appears to affect the DNase I digestion pattern in our experiments in the same way that other intercalating compounds affect DNase I digestion: producing a sequence specific enhancement or inhibition of digestion (23,24). These caffeine-enhanced or inhibited digestion sites are indicated by asterisks in Figs.…”
Section: Resultsmentioning
confidence: 82%
“…Instead, it strongly promotes nonspecific binding by UvrA as evidenced by the striking protection of the whole fragment (damaged or undamaged) from DNase I digestion when both UvrA and caffeine are present. We can also detect caffeine-dependent binding of (20)(21)(22), and it appears to affect the DNase I digestion pattern in our experiments in the same way that other intercalating compounds affect DNase I digestion: producing a sequence specific enhancement or inhibition of digestion (23,24). These caffeine-enhanced or inhibited digestion sites are indicated by asterisks in Figs.…”
Section: Resultsmentioning
confidence: 82%
“…( 54) actinomycin D, 55) theaflavin, 56) novatrone (mitoxantrone) 57,58) and aromatic drugs [59][60] have been studied by NMR spectroscopy. It has been suggested that the imidazole moiety of caffeine is involved in the interaction with aromatic species.…”
Section: Stability Constants Of Rf-caffeine Complexmentioning
confidence: 99%
“…However, the suggestion [19][20][21]23,[35][36][37][38][39][40] that hetero-association is the only mechanism for the protective effect in DrugInterceptor-Receptor systems is primary based on the assumption that the interceptor molecule does not (or very weakly) interact with the bio-receptor. On the other hand, it has been shown that both CAF [43,[59][60][61] and RBF [50] molecules are able to bind with DNA in a fashion very similar to intercalation or by external binding. A quantitative estimate of the DNA complexation constants gives the same order of magnitude as for the hetero-association constants with various drugs (~10 2 … 10 3 M − 1 for CAF [43] and~10 3 …10 4 M − 1 for RBF [50]).…”
Section: Introductionmentioning
confidence: 99%